Analisis Faktor-Faktor Yang Mempengaruhi KinerjaSistem Informasi Akuntansi ( Studi Pada Rumah Sakit PKU Muhammadiyah Surakarta dan Rumah Sakit ORTOPEDI PROF. DR. R. Soeharso Surakarta) - Darmestika, Ariani Khusna, Drs. Suyatmim Waskito Adi, M.Si (2017)
The purpose of this research to examine and analyze of the involvement of users in the development system, training and education programs, top management support, personal technical capability toward and formalization of the system development the performance of accounting information systems.This type of research is quantitative. The population in this study were all employees of PKU Muhammadiyah Hospital and Orthopaedic Hospital Prof.Dr.R Soeharso in Surakarta in the accounting, finance, tax, and other installations was 46 respondents.Collection data the method used was in questionnaire. The sampling technique used in this study is purposive sampling. Data were analyzed using SPSS version 22.0. The results showed that user Engagement in the Development System and formalization of the system development does not affect the performance of accounting information systems does not affect the performance of accounting information systems. While training and education programs performance, the support of top management and the ability of the technique of personal influence affect the accounting information system.